1351 Primary Pituitary Abscess Presenting as An Isolated Bitemporal Hemianopia. (12th October 2021) - Tan, E; Zammit, A
Abstract: Pituitary abscesses are rare yet life-threatening entities. Most common presenting features are headache, hypopituitarism, and visual changes. Majority of patients are found to have a predisposing risk factor, such as a pre-existing pituitary lesion, recent pituitary surgery or irradiation, or a primary source of infection. We present the case of a 53-year-old male with a spontaneous pituitary abscess, who presented with an isolated bitemporal hemianopia, but was otherwise asymptomatic with no known risk factors. Magnetic resonance imaging showed a sellar and suprasellar mass, thought to be a pituitary macroadenoma. He underwent endoscopic transsphenoidal adenectomy and cystic fluid was seen intraoperatively. Microbiology analysis showed Staphylococcus Aureus, and a course of intravenous ceftriaxone was commenced. Histopathology reported no evidence of adenoma and impression was of a pituitary abscess. Following transsphenoidal resection and commencement of antibiotic therapy, the bitemporal hemianopia resolved. We therefore report a rare case of primary pituitary abscess and emphasise the importance of including this condition as a differential diagnosis in any patient with a visual deficit or new pituitary lesion.